Compliance and Experience of Quarantine during the 1st Wave of COVID-19 Pandemic in Mumbai - Shilpa Nellikkal; Rujuta Hadaye; Apurva Lonikar (Indian Journal of Public Health, 2024)
Background: At the beginning of the pandemic, quarantine was thought to be the most effective way to contain the spread of the virus among international travelers and any potential carriers. Objectives: This study assessed the type of quarantine, compliance to quarantine measures (QM), mood, and any social stigma faced during that period. Materials and Methods: After approval from the institutional ethics committee, a telephonic interview survey was conducted. Individuals above 18 years of age visiting the only functioning COVID-19 screening outpatient department at Kasturba Hospital between March 1, 2020, and March 10, 2020 were included in the study. A total of 263 individuals were interviewed. Results: Out of 263 respondents, 71% and 34% of individuals had a history of international travel and contact history, respectively. Only 63% had read the guidelines on home QM. Among individuals quarantined, 127 that living alone in their apartments, 60 were in a single room with relatives outside, 37 were living with family members because they did not have another room, and 39 were staying in a facility quarantine center. On assessing the QM followed, wearing a mask was the least followed (46%). The average score of compliance to QM was 82.6%. Seventy-two per cent rated their mood as “5” on a scale of 1–10. Social stigma was reported by 7.6% of respondents. Conclusion: Among the early set of quarantined individuals in the city during the first wave of the pandemic, average score of compliance to QM was high even though lesser people recalled reading the guideline on home QM.